Should failure to protect laws include physical and emotional sibling violence?. Issue 1 (5th April 2019) - Perkins, Nathan H.; Barry, Johanna E.
Abstract: Physical and emotional sibling violence is a problematic occurrence for many children, adults, and families, yet this form of violence rarely falls within the purview of state laws and policies. Failure to protect laws offer one avenue through which sibling violence can be addressed by holding parents and caregivers accountable for harm that occurs to a child in their custody. This article provides background information on physical and emotional sibling violence as well as a general overview of failure to protect laws in the context of intimate partner violence with particular consideration of these laws in addressing sibling violence. In addition, the role social work practitioners can play in intervening and addressing sibling violence through psychoeducation leading to policy (i.e., failure to act laws) is presented.